Association of the combined parameters including the frequency of primary cilia, PD-L1, Smoothened protein, membranous β-catenin and cytoplasmic β-catenin expression with the outcome of patients with clear cell renal cell carcinoma - Rozsypalova, Aneta; Rosova, Blanka; Filipova, Alzbeta; Nikolov, Dimitar Hadzi; Chloupkova, Renata; Richter, Igor; Zachoval, Roman; Matej, Radoslav; Melichar, Bohuslav; Buchler, Tomas; Dvorak, Josef (Biomedical papers, 2025)
Aims. The objective of this study was to investigate the association and combined prognostic significance of the PD-L1, Smoothened protein and β-catenin expressions in patients with clear cell renal cell carcinoma (ccRCC). Methods. The PD-L1, Smoothened protein and β-catenin expression were evaluated in 104 ccRCC patients. All studied tumor samples were acquired from nephrectomy specimens of primary tumors and not from biopsies or metastases. An indirect immunohistochemistry using polyclonal rabbit anti-Smoothened antibody, monoclonal mouse anti-human β-catenin-1 antibody, immunohistochemical assay PD-L1 28-8 pharmDx using monoclonal rabbit anti-PD-L1 antibody and anti-VHL (C- terminal) rabbit antibody was used. Immunohistochemistry was scored semiquantitavely. Results. Median overall survival (OS) was significantly better in patients with lower PD-L1 expression (≤5%), Smoothened protein (SMO) expression (<5%) or cytoplasmic β-catenin expression (≤75%) than in patients with higher expressions of these biomarkers (P<0.001, P=0.047, and P<0.001, respectively). Membranous β-catenin showed an opposite effect with its lower expression (≤75%) being associated with longer OS (P=0.020). There was significant association between PD-1 and PD-L1 expression (P=0.007) and significant association of tumor grade (WHO 2016) with membranous β-catenin (P<0.001), cytoplasmic β-catenin (P=0.005), pVHL (P=0.042), PD-L1 (P=0.049) and PD-1 (P=0.028) expression. Conclusion. The present study provides the first data on the potential association and combined prognostic significance of frequency of primary cilia, PD-L1, Smoothened protein and β-catenin expression with the outcome in clear cell renal cell carcinoma.
Keywords: clear cell renal carcinoma; primary cilia; programmed cell death protein ligand 1; smoothened protein; membranous β-catenin; cytoplasmic β-catenin